Pendidikan yang Berpihak pada Peserta Didik dan Memerdekakan Peserta Didik dalam Pendidikan Abad ke-21 - Anggraini Pratiwi; Liesna Andriany (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to find out how education is impartial and liberating for students by developing a more inclusive and effective education system in the modern era. The research method used is Library Research or library research. This means that the data obtained in this research is not based on the perception or subjective views of the researcher, but is based on existing conceptual and theoretical facts. The results of the research show an increase in various aspects of learning such as students' motivation and interest in learning. The implementation of education that focuses on students plays an important role in helping to form individuals who are ready and resilient to face the future. Challenges faced include training teachers to use new technology and teaching methods effectively, as well as providing adequate infrastructure in schools, especially in less developed areas.